Late Saxon crop processing at Wharram Percy: new radiocarbon dates from the South Manor site - McKerracher, Mark; Croft, Bob; Stamper, Paul; Wrathmell, Stuart (Medieval Settlement Research, 2021)
Charred plant remains from the South Manor site - at the excavated medieval settlement of Wharram Percy, Yorkshire - were radiocarbon-dated by the Feeding Anglo-Saxon England project. These new radiocarbon dates suggest that a crop processing oven previously associated with the twelfth- to thirteenth-century manorial phase is now most plausibly dated to the late tenth century, and also that crops were probably being processed in the vicinity of a black loam layer by the ninth century. This evidence could indicate ’high status’ and/or specialised activity in this ninth- to tenth-century phase.